Rekrutmen Petugas Pendataan Registrasi Sosial Ekonomi Dengan Metode Multi Factor Evaluation Process - Deni Apriadi; Alfiarini Alfiarini (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
In 2022, the Central Statistics Agency (BPS) will carry out data collection activities for Socio-Economic Registration, where data collection for the entire population of Indonesia consists of profiles, social conditions, economy and welfare levels. This activity is one of the government's efforts to build a single population database. The implementation of good census activities can be used by the government in making policies in development. One of the successes in Regsosek activities is determined by the methods used in recruitment. To support the recruitment process for Regsosek officers, a computerized system is needed. Decision Support System is one of the systems that can be used to recruit Regsosek Officers. With the decision support system, the criteria that have been determined by BPS can be processed properly so as to produce best decision that suit the needs. There are many methods that can be used in a Decision Support System, one of which is the MFEP method. This method in its assessment can be done objectively and intuitively for factors that are considered important. In the Multi Factor Evaluation Process (MFEP) method, each criterion is given a weight according to the level of importance. In this study the criteria used were administrative selection, pretest, interview, education, age and health. With a decision support system that uses the MFEP method, it can help BPS produce decision solutions in selecting the best Regsosek officers based on predetermined criteria.